Electroacupuncture in non-surgical management of lumbar spinal stenosis: mechanistic potential in attenuating ligamentum flavum thickening via inflammatory factor modulation - Shi, Hao-Xin; Gao, Yu-Jun; Wang, Shu-Ren (Frontiers in Immunology, 2025)
Lumbar Spinal Stenosis (LSS) is a prevalent spinal disorder mainly induced by degenerative changes in the spine, which lead to nerve root compression. This results in symptoms such as lower back pain, numbness of the lower limbs, and difficulty in walking. The thickening of the ligamentum flavum (LF) is a crucial pathological feature of LSS and is closely linked to inflammatory responses. Electroacupuncture (EA), a form of traditional Chinese medical therapy, has garnered increasing recognition in modern medicine in recent years. It has shown notable efficacy in alleviating pain and enhancing function. EA achieves these effects by modulating inflammatory cytokines, reducing pro-inflammatory markers such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1le, and interleukin-6 (IL-6), while increasing anti-inflammatory cytokines like interleukin-10 (IL-10). Additionally, EA may inhibit LF thickening by suppressing signaling pathways, specifically the nuclear factor-κB (NF-κB) pathway, the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway, and the mitogen-activated protein kinase (MAPK) pathway. Clinical studies indicate that when EA is combined with other treatment modalities, it can significantly reduce pain and improve functional status in patients with LSS, thus enhancing their quality of life. Although the mechanisms underlying the effects of EA in the treatment of LSS warrant further exploration, its ability to regulate inflammatory responses through multiple pathways and promote tissue repair provides new perspectives and directions for the non-surgical management of LSS. This review encapsulates the application of EA in LSS and explores its potential mechanisms in mitigating LF thickening through the modulation of inflammatory cytokines. The aim is to offer a reference for future research and clinical practice.